2016
DOI: 10.1093/ecco-jcc/jjw051
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF Therapy Response in Patients with Ulcerative Colitis Is Associated with Colonic Antimicrobial Peptide Expression and Microbiota Composition

Abstract: Anti-TNF therapy responders and non-responders display distinctly separate patterns of mucosal AMP expression and gut microbiota before treatment start. This indicates that intestinal antimicrobial/microbial composition can influence treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 54 publications
9
136
3
4
Order By: Relevance
“…In particular, a lower dysbiosis index and higher amount of Faecalibacterium prausnitzii (Firmicutes) in responders compared with nonresponders at baseline was found. F. prausnitzii increased also during induction therapy in responders, indicating this species as a biomarker of treatment effectiveness . Consistent with several studies, F. prausnitzii contributes to the reduction of disease activity by producing butyrate, a SCFA, which inhibits the differentiation of Th17 cells and increases Treg cells …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Ibdsupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, a lower dysbiosis index and higher amount of Faecalibacterium prausnitzii (Firmicutes) in responders compared with nonresponders at baseline was found. F. prausnitzii increased also during induction therapy in responders, indicating this species as a biomarker of treatment effectiveness . Consistent with several studies, F. prausnitzii contributes to the reduction of disease activity by producing butyrate, a SCFA, which inhibits the differentiation of Th17 cells and increases Treg cells …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Ibdsupporting
confidence: 85%
“…F. prausnitzii increased also during induction therapy in responders, indicating this species as a biomarker of treatment effectiveness. 57 Consistent with several studies, F. prausnitzii contributes to the reduction of disease activity by producing butyrate, a SCFA, which inhibits the differentiation of Th17 cells and increases Treg cells. 58 Recently, Yilmaz and collaborators published a similar paper focused on the role of microbiota composition in two independent long-term IBD cohorts (cohort 1 = 346 patients; cohort 2 = 156 patients).…”
Section: Intestinal Microbiota and Immunosuppresant Drugssupporting
confidence: 84%
See 1 more Smart Citation
“…Week two concentrations of FC (AUC 0.82 and 0.61), faecal lactoferrin (AUC 0.84 and 0.80) and the dimeric M2 isoform of pyruvate kinase (AUC 0.88 and 0.78) could accurately predict both clinical and endoscopic response to IFX induction treatment . Finally, several authors have reported the association between low post‐induction FC levels and the decrease between baseline and post‐induction FC values and subsequent sustained response …”
Section: Resultsmentioning
confidence: 96%
“…Recent evidence, however, shows that mucosal expression patterns of certain defensins can be used to predict the potential efficacy of anti-TNF treatment. More specifically, it was found that a positive response to anti-TNF therapy was associated with increased mucosal expression of HD5 (Magnusson et al, 2016). …”
Section: Clinical Applicationsmentioning
confidence: 99%